Interest of Food and Beverage MSMEs in Becoming Customers of Sharia Banks: The Role of Inclusion and Literacy - Anis Tri Rahmawati; Khusnudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The aim of this research is to analyze the influence of sharia financial inclusion and literacy on the interest of micro, small and medium enterprises (MSMEs) in the food and beverage sector of Malang City to become sharia bank customers. This research uses quantitative methods with descriptive and verification approaches. Data was obtained through a survey involving 100 respondents who were MSME players in the sector. The results of this research show that both inclusion and sharia financial literacy have a positive and significant influence on the interest of MSMEs to become sharia bank customers, both partially and simultaneously. With a coefficient of determination of 74%, these two independent variables are able to significantly explain the interest in becoming a sharia bank customer. This research emphasizes the importance of increasing accessibility and public understanding of sharia financial services to encourage MSME involvement in the sharia-based financial ecosystem.